PELATIHAN KEWIRAUSAHAAN BERDASARKAN KOMPETENSI DAN KESIAPAN KERJA KEPADA SISWA-SISWI SMKN 02 KOTA BATAM PROVINSI KEPULAUAN RIAU - Wahyudi Ilham (JURNAL KEKER WISATA, 2024)
This service investigates the entrepreneurial readiness attitudes of Vocational High School (SMKN 2 Batam) students based on their abilities and work motivation. The purpose of this study is to examine the extent to which the skills students acquire at SMKN influence their preparation for business management and the workforce. The research methods used included questionnaires and qualitative data analysis of his SMKN 2 Batam students from different professional programs. The survey includes questions regarding skills acquired during training at SMKN, attitudes toward entrepreneurial preparation and job readiness. Descriptive analysis is used to assess the relationship between competency, entrepreneurial readiness, and job readiness. The findings show that there is a positive relationship between the skills students acquire at SMKN and their attitudes toward entrepreneurial preparation. Furthermore, high skills also help improve work motivation. These results provide a deeper understanding of how training at SMKN can effectively influence students' attitudes toward entrepreneurship and job readiness. This study makes an important contribution in the context of SMKN curriculum development, showing that competencies play an important role in shaping attitudes towards entrepreneurial preparation and preparing students for the dynamics of the world of work.is highlighted. The implications of these findings may help design educational programs focused on developing skills that support SMKN students' entrepreneurial success and job readiness.